Why does pollen morphology vary? Evolutionary dynamics and morphospace occupation in the largest angiosperm order (Asterales) - Jardine, Phillip E. (2022)
Morphological diversity (disparity) is a key component of biodiversity and increasingly a focus of botanical research. Despite the wide range of morphologies represented by pollen grains, to date there are few studies focused on the controls on pollen disparity and morphospace occupation, and fewer still considering these parameters in a phylogenetic framework. Here, we analyse morphospace occupation, disparity and rates of morphological evolution in Asterales pollen, in a phylogenetic context. We use a dataset comprising 113 taxa from across the Asterales phylogeny, with pollen morphology described using 28 discrete characters. The Asterales pollen morphospace is phylogenetically structured around groups of related taxa, consistent with punctuated bursts of morphological evolution at key points in the Asterales phylogeny. There is no substantial difference in disparity among these groups of taxa, despite large differences in species richness and biogeographic range. There is also mixed evidence for whole-genome duplication as a driver of Asterales pollen morphological evolution. Our results highlight the importance of evolutionary history for structuring pollen morphospace. Our study is consistent with others that have shown a decoupling of biodiversity parameters, and reinforces the need to focus on disparity as a key botanical metric in its own right.